Exploring the effect of previous inactivated influenza vaccination on seasonal influenza vaccine effectiveness against medically attended influenza: results of the European I-MOVE multicentre test-negative case-control study, 2011/2012-2016/2017 - Valenciano, Marta (2018)
Free PMC Article: https://www.ncbi.nlm.nih.gov/pmc/articles/PMC6086844/